The dominant driving force for supercontinent breakup: Plume push or subduction retreat? - Zhang, Nan; Dang, Z.; Huang, C.; Li, Zheng-Xiang (Elsevier, 2018)
Understanding the dominant force responsible for supercontinent breakup is crucial for establishing Earth's geodynamic evolution that includes supercontinent cycles and plate tectonics. Conventionally, two forces have been considered: the push by mantle plumes from the sub-continental mantle which is called the active force for breakup, and the dragging force from oceanic subduction retreat which is called the passive force for breakup. However, the relative importance of these two forces is unclear. Here we model the supercontinent breakup coupled with global mantle convection in order to address this question. Our global model features a spherical harmonic degree-2 structure, which includes a major subduction girdle and two large upwelling (superplume) systems. Based on this global mantle structure, we examine the distribution of extensional stress applied to the supercontinent by both sub-supercontinent mantle upwellings and subduction retreat at the supercontinent peripheral. Our results show that: (1) at the center half of the supercontinent, plume push stress is ~3 times larger than the stress induced by subduction retreat; (2) an average hot anomaly of no higher than 50 K beneath the supercontinent can produce a push force strong enough to cause the initialization of supercontinent breakup; (3) the extensional stress induced by subduction retreat concentrates on a ~600 km wide zone on the boundary of the supercontinent, but has far less impact to the interior of the supercontinent. We therefore conclude that although circum-supercontinent subduction retreat assists supercontinent breakup, sub-supercontinent mantle upwelling is the essential force.